Mobility Challenges Faced by Rural Women and the Implementation of the National Transport Policy in Busega District, Tanzania (Tanzania Journal for Population studies and Development, 2023)
This article is a product of a study that sought to analyse mobility challenges faced by rural women in Busega District, Tanzania, and examine the practice of implementing the National Transport Policy of 2003. Through adopting the intersectionality theory, the study sought to establish a connection between the implementation of the National Transport Policy (NTP) and its potential to improve the mobility of rural women. The study utilized a cross-sectional research design to collect data from a sample of 210 respondents through a household survey, interviews, focus group discussions, non-participant observation, and documentary review. Thematic analysis was applied to qualitative data, while descriptive statistics and Chi-square test were used for quantitative data. Based on the distribution analysis, it is evident that the majority of rural women were compelled to walk a long distance to access public transportation services. In addition, the Chi-square test results indicate a statistically significant difference at p